Profilbiegen mit kinematischer Gestalterzeugung - Arnet, Horst (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1999)
As part of the work, a new profile bending process was developed, in which the profiles are pressed into an elastic polyurethane matrix by means of a bending roller and can thus be flexibly bent using defined tool relative movements between the roller and the matrix. Due to the kinematic design and the associated flexibility, the developed technology is particularly suitable for the generation of variable curvature curves that vary over the profile length for small to medium lot sizes. The basic investigations carried out show a strong dependence of the locally achieved curvature on the respective immersion depth, on the cross-sectional geometry and on the material properties of the profile, on the current profile contour in the area of the contact surface of the profile on the die and on the position on the die. Only knowledge of the real position of the strain-free fiber in the profile creates the prerequisite for an assignment between profile and tool coordinates, which is required for process control. Alternatively, the method of finite elements or neural networks can be used to calculate the required tool relative movements. Both approaches were implemented, implemented in the planning system and verified experimentally. Using the example of producing a frame structure from curved profiles, it was demonstrated how a new bending task can be realized in a short time by using the flexible technology and the developed planning metho